High-toughness low-alloy corrosion-resistant steel for photovoltaic support and manufacturing method of high-toughness low-alloy corrosion-resistant steel
A high-strength, low-alloy corrosion-resistant steel for photovoltaic brackets is developed with controlled elemental compositions and manufacturing processes, addressing high production costs and environmental issues, achieving enhanced mechanical properties and efficiency.
Patent Information
- Application Number
- CN202411314075.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Existing steels used for photovoltaic brackets contain high amounts of precious metal elements, leading to high production costs, poor corrosion resistance and toughness, and difficulty in manufacturing, with environmental pollution issues from hot-dip galvanizing and high maintenance requirements.
A high-strength, low-alloy corrosion-resistant steel with controlled compositions of C, Si, Mn, P, S, Cu, Cr, Ti, Al, N, and B, manufactured through specific hot metal pretreatment, smelting, refining, and rolling processes to achieve fine grains and stable mechanical properties, reducing the need for post-pickling and painting.
The steel exhibits high strength, toughness, and corrosion resistance, with a lightweight design that reduces maintenance and production costs, while ensuring high production efficiency and environmental friendliness.
Smart Images

Figure CN119194290A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled steel strip manufacturing, and specifically relates to a high-strength and toughness low-alloy corrosion-resistant steel for a photovoltaic bracket and a manufacturing method thereof. Background Art
[0002] Nowadays, driven by the dual carbon and energy transformation goals, countries around the world attach great importance to the development of renewable energy. Solar energy is the most abundant renewable energy, and it is also the safest and cleanest energy. Solar photovoltaic power generation is a highlight in the field of new energy. Since 2006, the global solar photovoltaic installed capacity has been on the rise, with strong development momentum.
[0003] Photovoltaic brackets are special structural parts designed for placing, installing and fixing solar cell modules in photovoltaic power generation systems. Due to the scarcity of land resources, special areas such as deserts, Gobi, wastelands, tidal flats, offshore, coal and oil mining subsidence areas, saline-alkali land, etc. are becoming the main land for photovoltaic power generation systems. Photovoltaic brackets are exposed to wind, rain, snow, strong sunlight, high and low temperatures all year round in the open and harsh outdoor environments mentioned above, and are subjected to self-weight loads, wind loads, snow loads, and earthquake loads. In order to ensure the long-term stable and reliable operation of photovoltaic brackets in harsh environments, the steel used for photovoltaic brackets needs to have excellent corrosion resistance and high strength and toughness, and meet the requirements of corrosion resistance, tensile resistance, compression resistance, earthquake resistance, and sand erosion resistance.
[0004] At present, the steel used for photovoltaic brackets is mainly ordinary Q235B or Q355B hot-dip galvanized sheet, which has low strength, bulky structure, poor low-temperature impact toughness, and is easy to break in cold service environment. In addition, hot-dip galvanizing seriously pollutes the environment. When galvanizing at high temperature, NH4Cl in the plating agent is very easy to volatilize and decompose under heat, generating a large amount of NH4Cl smoke and irritating gases such as NH3 and HCl, which pollute the environment and produce zinc dust and zinc vapor, which endanger the health of operators. In addition, hot-dip galvanized sheet is easily hit and scratched during transportation and construction, causing the galvanized layer to fall off, and the later maintenance cost is high.
[0005] Weathering steel is becoming an ideal material for manufacturing photovoltaic brackets due to its unique corrosion resistance, high cost-effectiveness, environmental protection, energy saving and other advantages. However, the corrosion resistance, strength, toughness, hardness and cost of existing weathering steel cannot meet the service and economic requirements of photovoltaic brackets.
[0006] Chinese patent CN202211337425.2 discloses a high-strength, low-cost weathering steel for photovoltaic brackets and its preparation method and application, whose chemical composition includes C: ≤0.10%, Si: 0.02-0.50%, Mn: 0.80-2.00%, P≤0.030%, S≤0.005%, Cr: 0.20-0.80%, Cu: 0.20-0.60%, W: 0.05-0.50%, Als: 0.010-0.050%. Its preparation method adopts TMCP process, the steel plate is rapidly cooled to 100-300℃; the tempering temperature is 150-400℃, and the insulation time is 20-40min. The corrosion rate is ≤45% relative to Q345B ordinary steel, the yield strength is ≥690MPa, the tensile strength is 820-920MPa, the elongation is ≥18%, and the low-temperature impact energy is ≥200J.
[0007] However, the precious alloy element Cu content in the above-mentioned photovoltaic bracket steel is relatively high, which is prone to network crack defects during hot rolling and has a high cost. It contains expensive rare and strategic metal W, which further increases the alloy cost. The final cooling temperature of the steel plate is low, and it is difficult to control the plate shape and coil shape. In order to reduce the residual stress of the steel plate, tempering heat treatment is required, which increases the manufacturing cost and prolongs the production cycle. Compared with the corrosion rate of ordinary carbon steel Q345B of 33-45%, the corrosion resistance is low. The applicable temperature range of low-temperature impact energy is not clear, and users cannot select materials.
[0008] Chinese patent CN202410138488 discloses a weather-resistant hot-rolled steel strip and a production method thereof, and a weather-resistant steel strip, whose chemical composition includes C: 0.03-0.09%, Si: 0.05-0.30%, Mn: 0.4-1.8%, P: 0.04-0.07%, S: ≤0.0050%, Cr: 1.0-4.0%, Cu: 0.20-0.50%, Al: 0.01-0.05%, Ti: 0.09-0.15%, N: ≤0.0060%, yield strength ≥690MPa, tensile strength ≥800MPa, elongation ≥14%, -40℃ low-temperature impact energy ≥60J, weather resistance index I ≥8.0, and corrosion rate relative to Q355B ordinary low-alloy structural steel ≤35%.
[0009] However, the P content in the above-mentioned photovoltaic bracket steel is relatively high, the segregation of the ingot is relatively serious, the plasticity and low-temperature toughness of the steel are relatively poor, and various cracks are easily generated, which aggravates intergranular corrosion. At the same time, the content of precious alloy element Cu is relatively high, the product cost is high, and network crack defects are easily generated during hot rolling. The Ti content is relatively high, and it is easy to form coarse TiN precipitates that become stress concentration points and microcrack sources, reducing the forming and fatigue performance of the photovoltaic bracket. The recovery rate of Ti is unstable, and the mechanical properties fluctuate greatly, which increases the difficulty of photovoltaic bracket processing and reduces processing efficiency.
[0010] Chinese patent CN202210677545.0 discloses a high-strength, high-formability, super-atmospheric corrosion-resistant steel and a manufacturing method thereof, wherein the chemical composition includes C: 0.04-0.10%, Si≤0.50%, Mn: 0.20-1.80%, P≤0.03%, S≤0.01%, Al≤0.30%, Cu: 0.10-0.60%, Cr: 1.5-4.5%, Ti: 0.04-0.18%, N≤0.008%, Ni: 0-0.26%, Nb: 0-0.048%, V: 0-0.12%, Mg: 0-0.003%, Si+2Ni≥0.10%. Yield strength ≥700MPa, tensile strength ≥800MPa, yield strength ratio ≤0.90, elongation ≥18%, cold bending performance meets 180°D=1t bending, low-temperature impact toughness -20℃ impact energy is above 60J.
[0011] However, excessive Mn content in the above-mentioned photovoltaic bracket steel will reduce the plasticity and cold forming properties of the steel. A high Al content makes it easy to block the water nozzle during continuous casting. A high Cu content is easy to form copper brittle cracks and warping defects on the surface of the strip, deteriorating the surface quality. Cu is also a precious element, which increases the alloy cost. A high Ti content weakens its precipitation strengthening effect and significantly affects the low-temperature toughness of the steel. Ni is an important strategic material and is expensive. Adding Ni will greatly increase the alloy cost. Excessive Nb content will cause surface cracks, corner cracks and other defects in the continuous casting billet. Excessive V content will reduce the welding toughness of the steel. Nb and V are precious elements, which significantly increase the alloy cost. The boiling point of Mg is 1107℃. When Mg alloy is added to molten steel, Mg is rapidly vaporized in large quantities, the yield is extremely low, and the economy is poor. The low-temperature impact toughness can only meet the use requirements of -20℃, which is difficult to meet the service requirements of photovoltaic brackets in severe cold areas.
[0012] In summary, the steel used for photovoltaic brackets in the prior art contains more precious metal elements, which increases the production cost, and the corrosion resistance and toughness of the steel are poor. At the same time, the production of photovoltaic brackets in the prior art is difficult, the manufacturing cost is high, and the production efficiency is low, which needs to be improved. Summary of the invention
[0013] In order to solve all or part of the above problems, the purpose of the present invention is to provide a high-strength and low-alloy corrosion-resistant steel for photovoltaic brackets and a manufacturing method thereof, which can reduce manufacturing costs, achieve lightweight, and improve the corrosion resistance and toughness of the steel, while also reducing the production difficulty of photovoltaic brackets and improving production efficiency.
[0014] In a first aspect, the present invention provides a high-strength, toughness, low-alloy, corrosion-resistant steel for a photovoltaic bracket, wherein the composition of the high-strength, toughness, low-alloy, corrosion-resistant steel includes, by mass percentage: C: 0.17%-0.20%, Si: 0.80%-0.95%, Mn: 0.10%-0.19%, P: 0.031%-0.039%, S: 0.0020%-0.0030%, Cu: 0.13%-0.18%, Cr: 3.1%-3.3%, Ti: 0.010%-0.025%, Alt: 0.02%-0.06%, T[O]: 0.0010%-0.0020%, N: 0.0030%-0.0055%, B: 0.0021%-0.0031%, and the rest is Fe and unavoidable impurities;
[0015] Wherein, the high-strength and toughness low-alloy corrosion-resistant steel satisfies Ti / N≥3.4.
[0016] Optionally, the high-strength and tough low-alloy corrosion-resistant steel has the following properties:
[0017] Grain size ≥11;
[0018] Yield strength ≥750MPa, tensile strength ≥850MPa, elongation after fracture ≥18%, strength-ductility product ≥15.3 (GPa·%), 180°d=a cold bending test passed, -40℃ impact absorption energy ≥120J, Brinell hardness ≥245.
[0019] After 72 hours of periodic immersion in a NaHSO3 solution with an initial concentration of 0.01 mol / L, the corrosion rate relative to Q355B ordinary steel is ≤28%.
[0020] In a second aspect, the present invention provides a method for manufacturing high-strength and low-alloy corrosion-resistant steel for a photovoltaic bracket, comprising the following steps:
[0021] S1, through hot metal pretreatment desulfurization, top and bottom composite blowing converter smelting, LF refining, RH refining and slab continuous casting, to obtain a continuous casting billet with a thickness of 180-230 mm;
[0022] S2, hot-charge the continuous casting billet to the walking beam heating furnace for heating and heat preservation;
[0023] S3, rolling the continuous casting slab by a rough rolling mill to obtain a strip;
[0024] S4, rolling the strip by a finishing mill to obtain a hot-rolled steel strip;
[0025] S5, the hot rolled steel strip is cooled during transportation on a laminar cooling roller;
[0026] S6, coiling the hot-rolled steel strip into a hot-rolled steel coil by a coiler.
[0027] Optionally, in S2, the charging temperature of the continuous casting billet is controlled to be ≥550°C, and the time from the billet being discharged to the charging into the walking beam heating furnace is controlled to be ≤8 hours.
[0028] Optionally, in S2, the heating time of the continuous casting billet in the temperature range of 550℃-700℃ is controlled to be 60-67.5 minutes, the heating time in the temperature range of 700℃-1170±10℃ is controlled to be 75-90 minutes, the holding time in the temperature range of 1160℃-1180℃ is controlled to be 45-52.5 minutes, and the continuous casting billet outlet temperature is controlled to be 1160℃-1180℃, and the cumulative furnace residence time is 180-210 minutes.
[0029] Optionally, in S3, the continuous casting billet is rough rolled by 7 rough rolling passes, and the rough rolling start temperature is controlled to be 1110°C-1130°C and the rough rolling finish temperature is controlled to be 1040°C-1080°C.
[0030] Optionally, in S4, the strip is finish-rolled by a 7-stand finishing mill, and the finishing start temperature is controlled to be 980°C-1030°C, the finishing final temperature is controlled to be 830°C-870°C, and the thickness of the hot-rolled steel strip is controlled to be 4.0-6.0 mm.
[0031] Optionally, in S5, the cooling method of the hot-rolled steel strip on the laminar cooling roller is front-stage dense laminar cooling, and the flow ratio of the upper and lower header cooling water is controlled to be 10:12.
[0032] Optionally, in S6, during the coiling process of the hot-rolled steel strip, the coiling temperature of the hot-rolled steel strip is controlled to be 550°C-590°C.
[0033] It can be seen from the above technical scheme that the high-strength and low-alloy corrosion-resistant steel for photovoltaic brackets and the manufacturing method thereof provided by the present invention have the following advantages:
[0034] The low alloy corrosion resistant steel has low harmful and impurity elements, pure steel, fine grains, high strength and toughness. It can reduce weight by 36% by replacing Q235B galvanized sheet, with significant lightweight effect. The low alloy corrosion resistant steel has high hardness, and the photovoltaic bracket for Gobi desert made of it has strong resistance to wind and sand erosion. The low alloy corrosion resistant steel has high corrosion resistance, and the corrosion rate is ≤28% relative to Q355B ordinary steel.
[0035] At the same time, the low-alloy corrosion-resistant steel has moderate P and Al contents, low contents of precious alloying elements Cu and Ti, and does not contain Mg elements with a low boiling point, thus avoiding its adverse effects on plasticity, toughness, welding performance, hot-rolled surface quality, etc., making the mechanical properties of the low-alloy corrosion-resistant steel more stable, and easier to smelt and continuously cast, with less difficulty in controlling the plate and coil shapes, making the steel and photovoltaic brackets easier to manufacture, and having high production efficiency.
[0036] In addition, the low-alloy corrosion-resistant steel does not contain expensive rare and strategic metal W, and does not contain precious alloy elements such as Ni, Nb, V, and Mo. It has a low Mn content, which effectively reduces the alloy cost. At the same time, the photovoltaic bracket made of this low-alloy corrosion-resistant steel does not require post-pickling, painting, and maintenance, and has the advantages of energy saving, environmental protection, short delivery cycle, and low cost of use.
[0037] Other features and advantages of the present invention will be set forth in the description which follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings are used to provide a further understanding of the technical solution of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the technical solution of the present invention and do not constitute a limitation on the technical solution of the present invention.
[0039] Figure 1 Flow chart of a method for manufacturing high-strength and toughness low-alloy corrosion-resistant steel in an embodiment of the present invention;
[0040] Figure 2 This is a typical organization diagram of the high-strength, toughness, low-alloy, corrosion-resistant steel under a scanning electron microscope in an embodiment of the present invention. DETAILED DESCRIPTION
[0041] To make the purpose, technical solution and advantages of the present invention more clear, the embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other arbitrarily without conflict.
[0042] like Figure 1 , Figure 2 The embodiment of the present invention is shown, in which a high-strength and tough low-alloy corrosion-resistant steel for a photovoltaic bracket is disclosed. The composition of the high-strength and tough low-alloy corrosion-resistant steel includes, by mass percentage: C: 0.17%-0.20%, Si: 0.80%-0.95%, Mn: 0.10%-0.19%, P: 0.031%-0.039%, S: 0.0020%-0.0030%, Cu: 0.13%-0.18%, Cr: 3.1%-3.3%, Ti: 0.010%-0.025%, Alt: 0.02%-0.06%, T[O]: 0.0010%-0.0020%, N: 0.0030%-0.0055%, B: 0.0021%-0.0031%, and the rest is Fe and unavoidable impurities. At the same time, the low-alloy corrosion-resistant steel satisfies Ti / N≥3.4.
[0043] The reasons for limiting the chemical elements in this embodiment are as follows:
[0044] It has been found in practice that an effective and economical way to improve the strength of steel is to increase the C content. However, as the C content increases, the plasticity, impact toughness, welding performance, forming performance, and corrosion resistance of the steel will decrease. In order to make the tensile strength of the steel strip in this embodiment reach more than 850MPa, and comprehensively consider the processing performance, welding performance and corrosion resistance, while taking into account the economy, the present invention controls the C content in the range of 0.17%-0.20%.
[0045] It has been found in practice that Si is not a precious alloy element, and its solid solution strengthening coefficient in ferrite is higher than that of Mn. Si is very effective in improving strength and corrosion resistance, but too high Si content reduces material toughness and is not conducive to improving welding performance. In order to make the tensile strength of the steel strip of the present invention reach more than 850MPa, and comprehensively consider the processing performance, welding performance and corrosion resistance, while taking into account the economy, the present invention controls the Si content in the range of 0.80%-0.95%.
[0046] It has been found in practice that Mn can form substitutional solid solution in steel, which plays a role in solid solution strengthening and increases the yield strength and tensile strength linearly. Mn is an austenite-forming element, which has the function of stabilizing austenite, reducing the austenite transformation temperature, increasing the ferrite nucleation rate, and reducing the grain growth rate, that is, it has the function of refining grains. However, an increase in the Mn content can increase the C equivalent of the steel, which is not good for welding performance. In order to make the tensile strength of the steel strip of the present invention reach more than 850MPa, and comprehensively consider the processing performance and welding performance, while taking into account the economy, the present invention controls the Mn content in the range of 0.10%-0.19%.
[0047] It has been found in practice that the solid solution strengthening effect of P in steel is second only to C, and it can effectively improve the atmospheric corrosion resistance of steel. Among the many alloy elements that improve corrosion resistance, P is the most cost-effective element. However, P is easy to form and precipitate Fe3P in steel, which increases the brittleness of steel and is not conducive to improving the welding performance of steel. The diffusion rate of P in γ iron and α iron is low, and it is easy to form segregation, which has an adverse effect on the forming performance of steel. In order to make the tensile strength of the steel strip of the present invention reach more than 850MPa, and comprehensively consider the processing performance, welding performance and corrosion resistance, while taking into account the economy, the present invention controls the P content in the range of 0.031%-0.039%.
[0048] It has been found in practice that a higher S content can cause "hot brittleness" defects in steel. Adding Mn and S to the steel to form MnS plastic inclusions can reduce the harmful effects of S. However, during the rolling process, the MnS extending along the rolling direction tends to form a banded structure in the steel strip, reducing the transverse impact toughness and forming properties of the steel strip, while causing anisotropy of mechanical properties. S is harmful to the corrosion resistance of steel, and the sulfides in the steel can become the source of rust. Therefore, the S content should be reduced as much as possible, but if the S content is controlled too low, it will increase manufacturing costs and reduce production efficiency. Taking into account the uniformity of mechanical properties, processing properties and corrosion resistance of the high-strength and tough steel strip of the present invention, while taking into account economy and production efficiency, the present invention controls the S content in the range of 0.0020%-0.0030%.
[0049] It has been found in practice that Cu forms precipitates on the surface of steel and acts as a cathode to passivate the surface of the steel and accumulate in the rust layer, changing the structure of the rust layer and preventing Cl - Invades the matrix, so Cu is an effective element to improve the corrosion resistance of steel. However, Cu has a low melting point (1083°C), and is easily segregated at the grain boundary during the heating process of the continuous casting billet. Too high a Cu content will cause a network crack defect during hot rolling. Cu is also a relatively expensive alloying element, and too high a Cu content will increase the product cost. Taking into account the hot processing performance, surface quality and corrosion resistance of the high-strength and tough steel strip of the present invention, while taking into account the economy, the present invention controls the Cu content in the range of 0.13%-0.18%.
[0050] It has been found in practice that Cr has a solid solution strengthening effect, which can improve the hardenability and strength of steel, form a dense and uniform rust layer containing fine α-FeOOH on the surface of the substrate, accelerate the development of electrochemical corrosion products to a thermodynamically stable state, block the further penetration of corrosive media into the substrate, and reduce the corrosion rate of steel. However, when the Cr content is too high, carbides will precipitate at the grain boundaries, reduce the plasticity and toughness of the steel, deteriorate the forming performance and welding performance, and increase the alloy cost. In order to make the tensile strength of the steel strip of the present invention reach more than 850MPa, and comprehensively consider the corrosion resistance, plasticity and toughness, processing performance, welding performance, and economic efficiency, the present invention controls the Cr content in the range of 3.1%-3.3%.
[0051] It has been found in practice that TiN formed by Ti and N can inhibit the growth of austenite grains during the heating process of the continuous casting billet, which is beneficial to improving the strength and toughness and welding performance of the steel. Ti combines with N to form TiN before B, avoiding the formation of harmful BN, so that B can give full play to its beneficial role. If the Ti content is high, on the one hand, coarse TiN precipitates are easily formed, and become stress concentration points and microcrack sources, reducing the forming and fatigue performance of the photovoltaic bracket. On the other hand, the recovery rate of Ti is unstable, and the mechanical properties fluctuate greatly, which increases the difficulty of photovoltaic bracket processing and reduces processing efficiency. Taking into account the strength and toughness, welding performance, processing performance and use performance of the high-toughness steel strip with tensile strength of the present invention, the present invention controls the Ti content in the range of 0.010%-0.025%.
[0052] It has been found in practice that the fine AlN formed by Al and N can inhibit the growth of austenite grains during the heating process of the continuous casting billet, has the effect of refining the grains, and can improve the strength and toughness and welding performance of the steel. Al combines with O to form Al2O3 before B, avoiding B from being oxidized, so that B can give full play to its beneficial role. However, too high Al content will lead to the formation of more Al2O3 inclusions, which will reduce the purity of the steel and the impact performance, corrosion resistance and surface quality of the steel strip on the one hand, and on the other hand, it is very easy to block the water nozzle during continuous casting, increase the difficulty of production, reduce production efficiency, and increase the alloy cost and manufacturing cost. Taking into account the strength and toughness, welding performance, processing performance, impact performance, corrosion resistance and surface quality of the tensile strength high-toughness steel strip of the present invention, and taking into account the difficulty of production, production efficiency and economy, the present invention controls the Alt content in the range of 0.02%-0.06%.
[0053] It has been found in practice that oxygen is the heat source for converter steelmaking. It oxidizes and removes impurity elements in molten steel, but deoxidation is necessary in the later stage of steelmaking, otherwise the high oxygen content will make it impossible to continuously cast the molten steel, and a large amount of oxidized inclusions will be formed in the steel, reducing the purity of the steel and deteriorating the performance of the steel. Therefore, the oxygen content in the steel should be reduced as much as possible, but too low an oxygen content will increase the difficulty of production, reduce production efficiency, and increase manufacturing costs. Taking into account the purity and comprehensive performance of the tensile strength and high-toughness steel strip of the present invention, and taking into account the difficulty of production, production efficiency, and economy, the present invention controls the T[O] content in the range of 0.0010%-0.0020%.
[0054] It has been found in practice that N is a harmful element in steel. Too high N content will reduce the purity of steel and deteriorate the performance of steel. Therefore, the N content in steel should be reduced as much as possible, but too low N content will increase the difficulty of refining production, reduce production efficiency, and increase manufacturing costs. Taking into account the purity and comprehensive performance of the high-strength and tough steel strip of the present invention, and taking into account the production difficulty, production efficiency, and economy, the present invention controls the N content in the range of 0.0030%-0.0055%.
[0055] It has been found in practice that trace amounts of B can improve the hardenability of steel, significantly increase strength and improve toughness. However, B is an element that is prone to segregation. When its content is high, it is easy to form a segregation structure composed of Fe3(B,C) and Fe 23 The network precipitates composed of (B, C) are brittle and hard, which can weaken the connection between the matrix and have an adverse effect on the plasticity and toughness of the steel. When the number of precipitates is large and the size is large, the impact is more significant. A higher B content will also lead to an increase in manufacturing costs. Taking into account the strength, plasticity and toughness of the high-strength and tough steel strip of the present invention, and taking into account the economy, the present invention controls the B content in the range of 0.0021%-0.0031%.
[0056] It has been found in practice that as Ti / N decreases, N in the steel cannot be completely fixed by Ti, and some N will form harmful BN with B, and the beneficial effect of B in significantly improving the strength of the steel and improving the toughness cannot be fully exerted. Taking into account the strength and toughness of the high-strength and tough steel strip of the present invention, the present invention controls Ti / N≥3.4.
[0057] In this embodiment, the selection of the above-mentioned C, Si, Mn, P, S, Cu, Cr, Ti, Alt, T[O], N, B, and Ti / N has a synergistic effect. By controlling the content of each element and Ti / N within the above-mentioned range, the solid solution strengthening, fine grain strengthening, and phase transformation strengthening effects can be fully exerted, so that the high-strength and toughness low-alloy corrosion-resistant steel for photovoltaic brackets has high purity, high strength and toughness, and excellent cold working performance.
[0058] Secondly, the selection of the above-mentioned Si, P, S, Cu, Cr, Alt, and T[O] element contents has a synergistic effect. By controlling the content of each element within the above-mentioned range, a dense inner rust layer can be formed on the surface of the steel matrix, so that the high-strength and toughness low-alloy corrosion-resistant steel has high corrosion resistance, does not require subsequent pickling, painting and maintenance, and is energy-saving and environmentally friendly.
[0059] At the same time, the selection of the above-mentioned C, Mn, S, Cu, Alt, and T[O] has a synergistic effect. By controlling the content of each element within the above-mentioned range, defects such as hot-rolled network cracks can be avoided, so that the high-strength and toughness low-alloy corrosion-resistant steel for the photovoltaic bracket has excellent hot processing properties and high surface quality, which can meet the stringent processing and service requirements of the photovoltaic bracket.
[0060] Moreover, the selection of all the above-mentioned element contents and Ti / N has a synergistic effect. By controlling all the element contents and Ti / N within the above-mentioned range, the high-strength, toughness, low-alloy corrosion-resistant steel used for the photovoltaic bracket has low processing difficulty, high production efficiency, low manufacturing cost and short delivery cycle.
[0061] The low alloy corrosion resistant steel in this embodiment has at least the following properties:
[0062] (1) The grain size of high-strength and tough low-alloy corrosion-resistant steel shall be ≥ grade 11.
[0063] (2) The yield strength of high-strength and tough low-alloy corrosion-resistant steel shall be ≥750MPa, the tensile strength shall be ≥850MPa, the elongation after fracture shall be ≥18%, the strength-ductility product shall be ≥15.3 (GPa·%), the 180°d=a cold bending test shall be qualified, the impact absorption energy at -40℃ shall be ≥120J, and the Brinell hardness shall be ≥245.
[0064] (3) After 72 hours of periodic immersion in a NaHSO3 solution with an initial concentration of 0.01 mol / L, the corrosion rate of high-strength and low-alloy corrosion-resistant steel is ≤28% relative to that of Q355B ordinary steel.
[0065] like Figure 1 As shown, this embodiment also discloses a method for manufacturing high-strength and low-alloy corrosion-resistant steel for photovoltaic brackets, comprising the following steps:
[0066] S1, through hot metal pretreatment desulfurization, top and bottom composite blowing converter smelting, LF refining, RH refining and slab continuous casting, to obtain continuous casting billet;
[0067] S2, hot-charge the continuous casting billet to the walking beam heating furnace for heating and heat preservation;
[0068] S3, rolling the continuous casting slab by a rough rolling mill to obtain a strip;
[0069] S4, rolling the strip by a finishing mill to obtain a hot-rolled steel strip;
[0070] S5, the hot rolled steel strip is cooled during transportation on a laminar cooling roller;
[0071] S6, coiling the hot-rolled steel strip into a hot-rolled steel coil by a coiler.
[0072] In S1, the composition of the continuous casting billet is as follows by mass percentage: C: 0.17%-0.20%, Si: 0.80%-0.95%, Mn: 0.10%-0.19%, P: 0.031%-0.039%, S: 0.0020%-0.0030%, Cu: 0.13%-0.18%, Cr: 3.1%-3.3%, Ti: 0.010%-0.025%, Alt: 0.02%-0.06%, T[O]: 0.0010%-0.0020%, N: 0.0030%-0.0055%, B: 0.0021%-0.0031%, and the rest is Fe and unavoidable impurities, and Ti / N in the continuous casting billet is ≥3.4.
[0073] In S1, the thickness of the continuous casting billet is 180-230 mm. It is found in practice that, under the premise of the width and length of the continuous casting billet being determined, the thicker the continuous casting billet is, the higher the output and yield rate are. However, the greater the mill load is, the greater the fluctuation of the final rolling temperature, microstructure and mechanical properties of the finished steel strip in the length direction is. The thickness of the continuous casting billet is also limited by the maximum outer diameter of the steel coil allowed by the coiler. Therefore, considering the above influences, the thickness of the continuous casting billet is controlled to be 180-230 mm in this embodiment.
[0074] In S2, the charging temperature of the continuous casting billet is controlled to be ≥550℃, and the time from the billet being discharged to the charging into the walking beam heating furnace is controlled to be ≤8 hours. It has been found in practice that, under the premise of matching the steelmaking and hot rolling capacity, the planned timing and stable production, when the charging temperature of the hot-rolled continuous casting billet is ≥550℃, the energy consumption and oxidation burning loss can be significantly reduced, and the cracking defect of the continuous casting billet can be avoided.
[0075] If the charging temperature of the continuous casting billet is less than 550°C, the energy consumption and oxidation burning loss will increase, and the cracking tendency of the continuous casting billet caused by thermal stress and structural stress will increase. Therefore, the present invention controls the charging temperature of the continuous casting billet to be ≥550°C.
[0076] If the time from the continuous casting billet to the furnace entry is ≤8 hours, the furnace charging temperature can be guaranteed to be ≥550°C, and the production efficiency is high. If the time from the continuous casting billet to the furnace entry is greater than 8 hours, the furnace charging temperature cannot be guaranteed to be ≥550°C, and the production efficiency is low. Therefore, the present invention controls the time from the continuous casting billet to the step-beam heating furnace to be ≤8 hours.
[0077] In S2, the heating time of the continuous casting billet in the temperature range of 550℃-700℃ is controlled to be 60-67.5 minutes, the heating time in the temperature range of 700℃-1170±10℃ is controlled to be 75-90 minutes, the holding time in the temperature range of 1160℃-1180℃ is controlled to be 45-52.5 minutes, and the continuous casting billet discharge temperature is controlled to be 1160℃-1180℃, and the cumulative furnace residence time is 180-210 minutes.
[0078] It has been found in practice that the chemical composition of the low alloy corrosion resistant steel in the present invention is special. The continuous casting billet has poor plasticity in the temperature range of 550℃-700℃, and thermal stress exists on the surface and the center due to the large temperature difference. If the heating time in this temperature range is shorter than 60 minutes, the risk of cracking of the continuous casting billet due to thermal stress increases. If the heating time in this temperature range is longer than 67.5 minutes, oxidation burning, decarburization, energy consumption increase, and output decreases. Therefore, the present invention controls the heating time of the continuous casting billet in the temperature range of 550℃-700℃ to be 60-67.5 minutes.
[0079] It has been found in practice that the plasticity of the continuous casting billet is improved in the temperature range of 700℃-1170±10℃, and a shorter heating time can be used, but thermal stress still exists. If the heating time in this temperature range is shorter than 75 minutes, the risk of cracking of the continuous casting billet due to thermal stress increases. If the heating time in this temperature range is longer than 90 minutes, oxidation burning, decarburization, energy consumption increase, and output decreases. Therefore, the present invention controls the heating time of the continuous casting billet in the temperature range of 700℃-1170±10℃ to be 75-90 minutes.
[0080] It has been found in practice that if the holding temperature and the furnace discharge temperature of the continuous casting billet are lower than 1160°C, the austenite grains can be refined, but the continuous casting billet has poor thermoplasticity, high deformation resistance, difficult thermal deformation, and low mill operating rate. If the holding temperature and the furnace discharge temperature of the continuous casting billet are higher than 1180°C, the austenite grains are easy to coarsen, but the thermoplasticity of the continuous casting billet is improved, the deformation resistance is reduced, it is easy to thermally deform, and the mill operating rate is high. Therefore, considering the above effects, the present invention controls the holding temperature and the furnace discharge temperature of the continuous casting billet to be 1160°C-1180°C.
[0081] If the holding time of the continuous casting billet in the temperature range of 1160℃-1180℃ is shorter than 45 minutes, and the cumulative furnace time is shorter than 180 minutes, its structure is not easy to be homogenized, the rolling energy consumption is high, and equipment accidents are prone to occur. If the holding time of the continuous casting billet in the temperature range of 1160℃-1180℃ is longer than 52.5 minutes, and the cumulative furnace time is longer than 210 minutes, oxidation burning, decarburization, energy consumption will increase, and the mill operation rate and production efficiency will decrease. Therefore, taking the above influences into consideration, the present invention controls the holding time of the continuous casting billet in the temperature range of 1160℃-1180℃ to be 45-52.5 minutes, the continuous casting billet out of the furnace temperature is 1160℃-1180℃, and the cumulative furnace time is 180-210 minutes.
[0082] In S3, the continuous casting billet is rough rolled through 7 rough rolling passes, and the rough rolling start temperature is controlled to be 1110°C-1130°C and the rough rolling finish temperature is controlled to be 1040°C-1080°C.
[0083] It has been found in practice that the main metallurgical purpose of rough rolling is to destroy the as-cast structure of the continuous casting billet, effectively refine the austenite grains through multiple recrystallizations, and obtain an austenite structure with uniform and fine grains. If the rough rolling start temperature is too high, uneven austenite grains will occur, resulting in differences in the strip structure and affecting the uniformity of the mechanical properties of the finished product. If the rough rolling start temperature is too low, the strip shape control becomes more difficult, the mill load and rolling energy consumption increase, and it is not conducive to smooth rolling. Therefore, taking the above influences into consideration, the present invention controls the rough rolling start temperature to 1110°C-1130°C, and the rough rolling final rolling temperature to 1040°C-1080°C.
[0084] In S4, the strip is finish-rolled by a 7-stand finishing mill, and the finishing rolling start temperature is controlled to be 980°C-1030°C, the finishing rolling final temperature is controlled to be 830°C-870°C, and the thickness of the hot-rolled steel strip is controlled to be 4.0-6.0 mm.
[0085] It has been found in practice that if the finishing rolling start temperature is too high, partial recrystallization will easily occur in the F1 and F2 finishing rolling stands, resulting in mixed crystal problems and differences in the structure of the finished steel strip and abnormal fluctuations in the mechanical properties. If the finishing rolling start temperature is too low, the desired final rolling temperature cannot be guaranteed. Therefore, considering the above factors comprehensively, the present invention controls the finishing rolling start temperature to 980°C-1030°C.
[0086] It has been found in practice that if the finishing rolling temperature is too high, the finished steel strip will be coarsened and the toughness will be reduced. If the finishing rolling temperature is too low, the strength of the finished steel strip will be increased and the plasticity will be reduced, and the strength-plasticity matching will be unreasonable. At the same time, the rolling stability of the finishing rolling unit will be reduced, and the difficulty of controlling the thickness accuracy, width accuracy and cross-sectional shape of the steel strip will increase. In serious cases, the scrap steel strip will be rolled and the equipment will be damaged. Taking the above factors into consideration, the present invention controls the finishing rolling temperature to be 830℃-870℃.
[0087] In S5, the cooling method of the hot-rolled steel strip on the laminar cooling roller is front-stage dense laminar cooling, and the flow ratio of the upper and lower header cooling water is controlled to be 10:12.
[0088] It has been found in practice that, compared with other cooling methods, the front-stage dense laminar cooling method is conducive to refining ferrite grains, so that the strength, toughness, plasticity and cold forming performance of the finished steel strip are well matched. Therefore, considering the above factors comprehensively, the cooling method of the hot-rolled steel strip on the laminar cooling roller of the present invention adopts the front-stage dense laminar cooling method.
[0089] It has been found in practice that if the cooling water flow rate ratio of the upper and lower headers is higher or lower than 10:12, the cooling rates of the upper and lower surfaces of the steel strip will be greatly different, resulting in fluctuations in the organization and mechanical properties, and at the same time increasing the difficulty of plate shape control. Therefore, taking the above factors into consideration, the present invention controls the cooling water flow rate ratio of the upper and lower headers to be 10:12.
[0090] In S6, during the hot-rolled steel strip coiling process, the hot-rolled steel strip coiling temperature is controlled to be 550°C-590°C.
[0091] It has been found in practice that by properly controlling the coiling temperature, the γ→α phase transformation temperature can be appropriately reduced, the α phase nucleation rate can be increased, the ferrite grains can be refined, and the proportion of bainite in the organization can be appropriately increased. The bainite grain size is finer than that of ferrite, about 1μm, and has a higher dislocation density, which can improve the comprehensive mechanical properties of the steel strip. In addition, the reasonable control of the coiling temperature is also a necessary measure to reduce the difficulty of controlling the plate shape and coil shape. Taking the above factors into consideration, the coiling temperature of the present invention is controlled to be 550℃-590℃.
[0092] In order to more clearly show the performance comparison between this embodiment and comparative example 1 (CN202211337425.2), comparative example 2 (CN202410138488), and comparative example 3 (CN202210677545.0), the specific parameter comparisons are shown in Tables 1 to 4:
[0093] Table 1 Comparison of chemical compositions (mass percentage) of the embodiments of the present invention and the comparative examples
[0094]
[0095] Table 2 Comparison of furnace charging and heating process parameters of the embodiments of the present invention and the comparative examples
[0096]
[0097] Table 3 Comparison of rolling and cooling process parameters of the embodiments of the present invention and the comparative examples
[0098]
[0099] Table 4 Performance comparison of the embodiments of the present invention and the comparative examples
[0100]
[0101] As shown in Tables 1 to 4, there are significant differences in the chemical composition, furnace loading, heating, rough rolling, finishing rolling, cooling and other process parameters between the embodiments of the present invention and the comparative examples, and there are also significant differences in various performances. The low-alloy corrosion-resistant steel in the present invention can better meet the new requirements for the development of photovoltaic brackets such as high strength and toughness, lightweight, high corrosion resistance, long life, easy manufacturing, low cost, high efficiency, painting-free, maintenance-free, energy saving, and environmental protection.
[0102] It can be seen from the above process that the low alloy corrosion resistant steel and its manufacturing method in the present invention optimize the design of the content of elements such as C, Si, Mn, P, S, Cu, Cr, Ti, Alt, T[O], N, B, and control Ti / N, continuous casting billet charging temperature, heating time in different temperature ranges, furnace discharge temperature, furnace residence time, rough rolling start and final rolling temperature, finishing rolling start and final rolling temperature, rolling pass, finished product thickness, cooling method, upper and lower header cooling water flow ratio and coiling temperature, so that the grain size of the finished steel is above grade 11, the yield strength is ≥750MPa, the tensile strength is ≥850MPa, the elongation after fracture is ≥18%, the strength-plasticity product is ≥15.3 (GPa·%), the 180°d=a cold bending test is qualified, the -40°C impact absorption energy is ≥120J, and the Brinell hardness is ≥245. After 72 hours of periodic immersion in a NaHSO3 solution with an initial concentration of 0.01 mol / L, the corrosion rate relative to Q355B ordinary steel is ≤28%.
[0103] The low alloy corrosion resistant steel in the present invention has low harmful and impurity element content, pure steel quality, high strength and toughness, and can reduce weight by 36% by replacing Q235B galvanized sheet, with significant lightweight effect. The low alloy corrosion resistant steel has strong corrosion resistance and excellent forming performance, and can meet the demanding processing and service requirements of photovoltaic brackets.
[0104] At the same time, the low-alloy corrosion-resistant steel has moderate P and Al contents, low Cu and Ti contents, and does not contain the low-boiling point element Mg, which avoids its adverse effects on plasticity, toughness, welding performance, surface quality, etc., making the mechanical properties more stable, and easier to smelt, continuously cast, and control the plate and coil shapes, thereby improving the production efficiency of steel and photovoltaic brackets.
[0105] In addition, the low-alloy corrosion-resistant steel does not contain precious alloy elements such as W, Ni, Nb, V, and Mo, and has a low Mn content, which effectively reduces the production cost of the alloy. At the same time, the photovoltaic bracket made of this low-alloy corrosion-resistant steel does not require subsequent pickling, painting, and maintenance, and has the advantages of energy saving, environmental protection, short delivery cycle, and low cost of use.
[0106] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in the present invention should have the common meanings understood by those skilled in the art to which the present invention belongs.
[0107] In addition, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. In the description of the present invention, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A high-strength, low-alloy, corrosion-resistant steel for photovoltaic brackets, characterized in that: The composition of the high-strength and toughness low-alloy corrosion-resistant steel includes, by mass percentage: C: 0.17%-0.20%, Si: 0.80%-0.95%, Mn: 0.10%-0.19%, P: 0.031%-0.039%, S: 0.0020%-0.0030%, Cu: 0.13%-0.18%, Cr: 3.1%-3.3%, Ti: 0.010%-0.025%, Alt: 0.02%-0.06%, T[O]: 0.0010%-0.0020%, N: 0.0030%-0.0055%, B: 0.0021%-0.0031%, and the rest is Fe and unavoidable impurities; Wherein, the high-strength and toughness low-alloy corrosion-resistant steel satisfies Ti / N≥3.
4.
2. The high-strength, low-alloy, corrosion-resistant steel according to claim 1, characterized in that: The high-strength and tough low-alloy corrosion-resistant steel has the following properties: Grain size ≥11; Yield strength ≥750MPa, tensile strength ≥850MPa, elongation after fracture ≥18%, strength-ductility product ≥15.3 (GPa·%), 180°d=a cold bending test passed, -40℃ impact absorption energy ≥120J, Brinell hardness ≥245. After 72 hours of periodic immersion in a NaHSO3 solution with an initial concentration of 0.01 mol / L, the corrosion rate relative to Q355B ordinary steel is ≤28%.
3. A method for manufacturing high-strength and tough low-alloy corrosion-resistant steel according to claim 1 or 2, characterized in that: The steps include: S1, through hot metal pretreatment desulfurization, top and bottom composite blowing converter smelting, LF refining, RH refining and slab continuous casting, to obtain a continuous casting billet with a thickness of 180-230 mm; S2, hot-charge the continuous casting billet to the walking beam heating furnace for heating and heat preservation; S3, rolling the continuous casting slab by a rough rolling mill to obtain a strip; S4, rolling the strip with a finishing mill to obtain a hot-rolled steel strip; S5, the hot rolled steel strip is cooled during transportation on a laminar cooling roller; S6, coiling the hot-rolled steel strip into a hot-rolled steel coil by a coiler.
4. The method for manufacturing high-strength and tough low-alloy corrosion-resistant steel according to claim 3, characterized in that: In S2, the charging temperature of the continuous casting billet is controlled to be ≥550°C, and the time from the billet being taken out to the billet being charged into the walking beam heating furnace is controlled to be ≤8 hours.
5. The method for manufacturing high-strength and tough low-alloy corrosion-resistant steel according to claim 4, characterized in that: In S2, the heating time of the continuous casting billet in the temperature range of 550℃-700℃ is controlled to be 60-67.5 minutes, the heating time in the temperature range of 700℃-1170±10℃ is controlled to be 75-90 minutes, the holding time in the temperature range of 1160℃-1180℃ is controlled to be 45-52.5 minutes, and the continuous casting billet discharge temperature is controlled to be 1160℃-1180℃, and the cumulative furnace residence time is 180-210 minutes.
6. The method for manufacturing high-strength and tough low-alloy corrosion-resistant steel according to claim 3, characterized in that: In S3, the continuous casting billet is rough rolled through 7 rough rolling passes, and the rough rolling start temperature is controlled to be 1110°C-1130°C and the rough rolling finish temperature is controlled to be 1040°C-1080°C.
7. The method for manufacturing high-strength and tough low-alloy corrosion-resistant steel according to claim 3, characterized in that: In S4, the strip is finish-rolled by a 7-stand finishing mill, and the finishing rolling start temperature is controlled to be 980°C-1030°C, the finishing rolling final temperature is controlled to be 830°C-870°C, and the thickness of the hot-rolled steel strip is controlled to be 4.0-6.0 mm.
8. The method for manufacturing high-strength and tough low-alloy corrosion-resistant steel according to claim 3, characterized in that: In S5, the cooling method of the hot-rolled steel strip on the laminar cooling roller is front-stage dense laminar cooling, and the flow ratio of the upper and lower header cooling water is controlled to be 10:
12.
9. The method for manufacturing high-strength and tough low-alloy corrosion-resistant steel according to claim 6, characterized in that: In S6, during the hot-rolled steel strip coiling process, the hot-rolled steel strip coiling temperature is controlled to be 550°C-590°C.
Citation Information
Patent Citations
High-strength and high-corrosion-resistance steel plate material with yield strength of 900 MPa and production method thereof
CN103290335A
Steel with high strength, high forming performance and super atmospheric corrosion resistance and manufacturing method thereof
CN115161551A
High-strength hot-rolled strip steel with high weather resistance and manufacturing method of high-strength hot-rolled strip steel
CN115161552A
High-corrosion-resistance hot-rolled weather-resistant steel plate for 800MPa-grade photovoltaic support and preparation method of high-corrosion-resistance hot-rolled weather-resistant steel plate
CN117535595A
Hot-rolled weather-resistant steel plate for thin-gauge 1000MPa-grade photovoltaic bracket and preparation method thereof
CN117535597A
